Inhibitory Effect of Abitylguanide on Adenovirus Replication - Galabov, Angel S.; Vassileva, Vesselina; Karabasheva, Vera (Drug Research, 2017)
N’N’-anhydro-bis(β-hydroxy-ethyl)biguanide.HCl (abitylguanide) demonstrated a marked inhibitory effect on replication in cell cultures of a broad spectrum of human adenoviruses both standard laboratory strains and strains isolated from epidemic keratoconjunctivitis patients. The strongest inhibitory activity was found in viruses belonging to subgroup C (Rosen’s subgroup III). The compound susceptible period of human adenovirus 5 replication in primary cell cultures of human embryo kidney cells included the total replication cycle and was especially pronounced during the exponential phase of the virus growth curve. Electron microscopy established that the compound decreased the percentage of cells in which mature or empty virions with the characteristic nuclear localization were observed; a complete absence of paracrystals was registered and the number of cells with virus particles arranged in crystals in the nucleoplasm was strongly decreased. Abitylguanide can be considered as a ligand of adenovirus capsid protein(s).
Keywords: abitylguanide; human adenoviruses; electron microscopy